Predicted waiting times for orthopaedic surgery: an urgent need to address the deficit in capacity. Issue 12 (14th December 2022) - Farrow, Luke; Jenkins, Paul J.; Dunstan, Edward; Murray, Alastair; Blyth, Mark J. G.; Simpson, A. Hamish R. W.; Clement, Nick D.
Abstract : Cite this article: Bone Joint Res 2022;11(12):890–892.